Azerbaijan : Enterprise Restructuring and Labor Redeployment, Volume 1, Main Report - World Bank (Washington, DC, 2012)
The main objective of this report is, first, to examine changes in the welfare and labor market status of workers in Azerbaijan, with concentration on large state-owned enterprises (SOEs) already displaced or which may be displaced because of enterprise restructuring and privatization. This includes identifying: a) dominant patterns in labor market behavior, b) changes in worker socioeconomic status in the wake of redundancy; and c) assistance received under enterprise social programs and other government social safety nets. Second, the study also explores patterns of job creation and job destruction, and the dynamics of labor demand, including any barriers to firm entry and growth. The study focuses largely on identifying informational and institutional gaps in elaborating a general labor redeployment program suitable for conditions in Azerbaijan. Suggestions for the introduction of labor redeployment activities and enterprise social plans are provided that would enable authorities to design relevant mitigating measures. The report concludes that findings indicate labor market interventions have great potential to improve labor market performance; however, whether or not this potential is realized depends on a number of factors, and numerous variables can intervene to affect the final outcome of their implementation. These include external factors such as stable macroeconomic conditions, a favorable investment climate with an enabling business environment, and a competitive product market. In addition, there are important internal factors: specifically, policy design and implementation. A significant share of the able-bodied population needs better employment opportunities, and state support is necessary to enhance workers' competitiveness in the labor market and assist job-seekers in their employment search.